Kesinai (Streblus Asper) Protease as a Potential Milk Coagulating Enzyme - Ahmed Idris, Yousif Mohamed (2000)
Leaf extract of plant kesinai (Streblus asper) contains a milk coagulating protease, which could be a potential rennet substitute. However, its potential has not been investigated and the protease has not been purified and characterised. Preparation of the crude leaf extract results in an undesirable, very dark brown colour and inhibition of this browning may enhance the use of the leaf extract. The browning inhibitors, citric acid, ascorbic acid, L-cysteine and sodium metabisulphite were used for prevention of browning and to obtain a crude extract with an acceptable colour. Metabisulphite was found to be an effective inhibitor of the enzymatic browning of the leaf extract. At 2 mM concentration it has inhibited browning and the extract obtained resulted in a white milk coagulum compared to the brown coloured coagulum of the brown extract. It is thermostable up to 85°C, with an optimum temperature at 70°C and its optimum pH is 7.2. Six mM added calcium chloride was optimum for its milk coagulation activity.Microstructure, texture and syneresis of the milk coagulum of the crude extract were assessed by Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), the Texture Analyser, and measurement of whey volume, respectively and were compared with that of calf rennet and Fromase. Kesinai coagulum appeared as a sponge-like when examined under SEM, while calf rennet and Fromase coagulum appeared as a fibrous network. Quantification results showed that porosity of kesinai coagulum is low, and significantly different from both of calf rennet and Fromase coagulum (P<0.05) and (P<0.01), respectively. Kesinai coagulum was soft, and its strength is significantly lower than that of calf rennet and Fromase coagulum (P< 0.01). Syneresis of its coagulum was low, and the whey volume as per cent of milk volume was 34.75% compared to 46.75% and 48.79%, for calf rennet and Fromase, respectively. The ratio of milk coagulation activity to proteolytic activity of the extract was very low (0.02) and the protein profile of the milk coagulum and whey on sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) showed that the protease was more proteolytic than calf rennet, and Fromase.The protease was purified by ultrafiltration (UF), Fast protein Liquid Chromatography (FPLC) gel filtration with Superose 6, FPLC ion exchange using MonoQ HR 5/5 and lsoelectric Focusing (IEF) using the Rotofor system, with a puritification fold of 25, and 18% recovery. The purified protease appeared as a single band on SDS-P AGE with a molecular weight of 31.3 kDa. Characterisation of the purified protease showed that it could be a serine protease with optimum pH of 7.2, stable in the pH range 5.0 -9.5, and its pI is 5.2. It is thermostable up to 85°C, with optimum temperature at 70°C. Zymogram analysis showed that protease activity is associated with milk coagulation activity. It is concluded that kesinai protease could be used in the production of short ripened cheese varieties.